The puzzle of economic growth and stalled health improvement in the Philippines. - Picazo, Oscar F. (2013)
This Policy Note provides an overview of the puzzle of economic growth and stalled health improvement in the country. The Philippine economy has grown respectably in the past few years, but the overall health status indicators have not markedly improved commensurate with that growth. The gap between the richest and the poorest Filipino households in terms of health financing, access to services, and health status has not also markedly improved. It is important to mull over the puzzle of economic growth and health inequity for several reasons. First, macroeconomic growth, international competitiveness, and financial stability are necessary conditions for development but they are not sufficient. The goal of a country`s growth efforts should be human development in a sustainable environment. Second, persistent social inequity within an improving economic environment breeds political instability, exclusion, and disenchantment among the poor, as well as crime and other social pathologies. Third, the lynchpin to any vibrant economy and polity is social participation, and more active social participation can only be achieved under a regime of more inclusive growth and reduced social inequity. And fourth, equity has also become a global benchmark, especially in health.
Keywords: Health insurance; Medical care